REVIEW ON MONOGRAPH BY N.A. MAGOMEDOV "REGIONAL AND INTERNATIONAL TRANSIT TRADE IN THE WESTERN CASPIAN REGION IN THE XVII-XVIII CENTURIES" - Kidirniazov, D S; Magaramov, S A (History, Archeology and Ethnography of the Caucasus, 2016)
-